Patient-reported harm following cancellation of planned surgery at a Danish university hospital: a cross-sectional study - Lone Nikolajsen; Pia Dreyer; Anette Viftrup; Sussie Laustsen; Maria Levin Pahle (BMJ Open)
Objectives To estimate the prevalence and severity of patient-reported physical and non-physical harm following surgery cancellation.Design Cross-sectional study.Setting A large Danish university hospital.Participants Patients (≥18 years) from various surgical specialities, such as orthopaedic, spinal, abdominal, gynaecological, thoracic, vascular and urological surgery whose surgery was cancelled <2 weeks prior to the scheduled date due to hospital-related causes.OutcomePatient-reported physical and non-physical harm, defined as physical worsening, emotional strain and other consequences, measured using a patient-reported survey.Results We identified 785 patients whose surgery was cancelled from 1 December 2021 to 1 June 2022, of whom 436 (55.5%) responded to the electronic survey. Physical worsening was reported by 42% and emotional strain by 48% of patients. One-third of patients reported an inability to continue daily activities, and 28% reported a need for an increased dose of analgesics. Emotional strain included various negative feelings such as being disappointed (59%) and lonely (31%). Furthermore, 44% of the respondents feared deterioration of their disease and 9% experienced anxiety of dying. The relative risk of emotional strain was higher in females than in males (54% vs 41%, adjusted relative risk (RR)=1.32 (1.08; 1.63)). A waiting period >30 days compared with ≤30 days was associated with a higher risk of physical worsening (25.3% vs 48.9%, adjusted RR=1.93 (1.42; 2.63)).Conclusions Harm, measured as physical worsening and emotional strain, is reported with severity by nearly half of respondents following cancellation.